[Translated article] Reasons for Referral and Epidemiological Characteristics of Patients Seen at a Dedicated Dermoscopy Unit in a Spanish Tertiary Care Hospital - P. García Piqueras; J. Ruiz Rivero; M. Guadalupe Izquierdo del Monte; J.A. Avilés-Izquierdo (Elsevier, 2022)
Dedicated dermoscopy units assess individuals at high risk for melanoma. Understanding the reasons for referral to these units and the epidemiological profile of referred patients can help optimize health care resources and determine who benefits most from dermoscopic evaluation. We analyzed reasons for referral and epidemiological characteristics of 413 patients with at least 1 high-risk factor for melanoma seen at a dedicated dermoscopy unit over a period of 10 years. We also analyzed the number of necessary excisions (NNE) for each melanoma diagnosed, histologic features, and associations between nonenvironmental factors and diagnosis. The main reasons for referral were a past history of melanoma (21.5%), changes detected by the patient or a relative (20%), clinical and/or dermoscopic findings suggestive of malignancy (19.4%), and a family history of melanoma (17.4%). Seventy-six of the 178 excised lesions were melanomas (NNE per melanoma detected, 2.34). Older age was the only risk factor significantly associated with the development of melanoma. Resumen: Las consultas monográficas de dermatoscopia digital están dirigidas a población con alto riesgo de melanoma. Conocer los motivos de derivación a estas consultas, así como las características epidemiológicas de los pacientes permite optimizar los recursos sanitarios y determinar qué pacientes se benefician más de esta técnica. Se analizaron los motivos de derivación y las características epidemiológicas de 413 pacientes atendidos en una consulta monográfica de dermatoscopia en un período de 10 años que presentaban al menos un criterio de alto riesgo de melanoma. También se analizó el número necesario de extirpaciones (NNE) por cada melanoma diagnosticado, sus características histológicas y qué variables no ambientales se asociaron con su diagnóstico. Los motivos de derivación más frecuentes fueron: antecedentes de melanoma previo (21,5%), cambios detectados por el paciente o su familia (20%), hallazgos clínicos y dermatoscópicos sospechosos de malignidad (19,4%) y antecedentes familiares de melanoma (17,4%); 76 de las 178 lesiones extirpadas fueron melanomas, obteniendo un NNE de 2,34. La edad avanzada fue el único factor de riesgo que se asoció de forma estadísticamente significativa con el desarrollo de melanoma.